2012
DOI: 10.1186/1752-153x-6-115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plant gums and saccharide materials in paint samples: comparison of GC-MS analytical procedures and databases

Abstract: BackgroundSaccharide materials have been used for centuries as binding media, to paint, write and illuminate manuscripts and to apply metallic leaf decorations. Although the technical literature often reports on the use of plant gums as binders, actually several other saccharide materials can be encountered in paint samples, not only as major binders, but also as additives. In the literature, there are a variety of analytical procedures that utilize GC-MS to characterize saccharide materials in paint samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 37 publications
6
51
0
Order By: Relevance
“…In these samples though, saponification, if it occurred, was not complete, as the ν as COO − bands of the glycerolipid materials were still very well visible in the spectra, and the ν as COO − bands of the lead carboxylates, if present, were not distinguishable from the amide II band. The sugar profiles that were observed were in perfect agreement with the presence of egg [18].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In these samples though, saponification, if it occurred, was not complete, as the ν as COO − bands of the glycerolipid materials were still very well visible in the spectra, and the ν as COO − bands of the lead carboxylates, if present, were not distinguishable from the amide II band. The sugar profiles that were observed were in perfect agreement with the presence of egg [18].…”
Section: Discussionsupporting
confidence: 71%
“…Elements in parentheses are present at trace levels. Pb (lead), Ca (calcium), Al (aluminium), Si (silicon), Fe (iron), Na (sodium), Mg (magnesium), K (potassium), S (sulphur), and Ba (barium) To determine the source of the saccharide materials, the data were compared to a database of saccharide profiles of reference materials [18], and when polysaccharide gums were hypothesised, they were identified using a decisional scheme that was reported in the literature [19]. The interpretation of the chromatograms relative to the lipid-resinous fractions was based on the recognition of molecular markers for resins and waxes and quantitative evaluation of mono and dicarboxylic acids for lipids [20].…”
Section: Table 2 Elements Identified By Sem-edx On the Nine Selected mentioning
confidence: 99%
“…Results from a previous stage of this research showed that sugars are found in many materials that can be encountered in a paint sample, such as organic colorants, plant resins and proteinaceous binders [28]. This indicates that a mixture of binders, which is extremely common in paintings, may lead to chromatogram profiles that are difficult to interpret when the overall composition of the organic materials is unknown.…”
Section: Resultsmentioning
confidence: 86%
“…In a previous stage of this research, it was suggested that the presence of a pigment in a paint layer containing a polysaccharide gum might cause modifications upon ageing [28]. For this reason, the effect of ageing in the presence of some pigments was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies of ancient binders acknowledge considerable difficulties in accurate identification due to the degradation of the original compounds, the mixture and interaction of materials present in the preparation, paint and protective layers, and the small sample size [25][26][27]. Besides these factors, often taken into account in such studies [28][29][30][31][32][33][34], are two other factors, not usually considered in literature, which may have a decisive influence on results: the difficulty in efficiently extracting organic binders from ancient paint samples, and the presence of organic material due to microbiological contamination.…”
Section: Introductionmentioning
confidence: 99%